Microbiologic contamination present in mops and cloths used for cleaning procedures in firefighters’ headquarters - Dias, Marta (2022)
Project "Occupational exposure of ambulance drivers to bioburden” (IPL/2020/BIO-AmbuDrivers_ESTeSL).